2003
DOI: 10.1046/j.1365-246x.2003.01823.x
|View full text |Cite
|
Sign up to set email alerts
|

Mantle circulation models with variational data assimilation: inferring past mantle flow and structure from plate motion histories and seismic tomography

Abstract: S U M M A R YMantle convection models require an initial condition some time in the past. Because this initial condition is unknown for Earth, we cannot infer the geological evolution of mantle flow from forward mantle convection calculations even for the most recent Mesozoic and Cenozoic geological history of our planet. Here we introduce a fluid dynamic inverse problem to constrain unknown mantle flow back in time from seismic tomographic observations of the mantle and reconstructions of past plate motions u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
166
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(181 citation statements)
references
References 95 publications
2
166
0
Order By: Relevance
“…It has also been shown that this technique can be extended to address the problem of having an incomplete picture of Earth's historical mantle structure (Bunge et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that this technique can be extended to address the problem of having an incomplete picture of Earth's historical mantle structure (Bunge et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The adjoint method for mantle circulation models (MCMs) has previously been utilised using both synthetic (Bunge et al 2003; and tomography derived (Horbach et al 2014) true state forward-adjoint mantle models. Further studies using a simplified adjoint calculation have also been conducted (Ismail-Zadeh et al 2004;Spasojevic et al 2009), which use a subset of the full adjoint equations.…”
Section: Introductionmentioning
confidence: 99%
“…by Bunge et al (2003), would take into account model errors, numerical approximations, errors on plate reconstructions and on the estimation of the current tomography-derived temperature field to provide the best fit given all sources of information.…”
mentioning
confidence: 99%
“…So far, variational data assimilation dominates over other methods to estimate 25 mantle circulation (Bunge et al, 2003;Horbach et al, 2014;Ghelichkhan and Bunge, 2016). To simplify the problem, they minimize the misfit between the final temperature field of the mantle circulation model and the one deduced from seismic tomography.…”
mentioning
confidence: 99%
See 1 more Smart Citation